Evaluation on H2O2‐aided ultrasonic pretreatment for cell disruption of Chlorella pyrenoidosa. Issue 3 (8th May 2017) - Duan, Zhipeng; Tan, Xiao; Dai, Kaiwen; Gu, Huihui; Yang, Hanpei
Abstract: In this work, Chlorella pyrenoidosa was chosen as model microalgae, and several pretreatments, including hydroxyl‐peroxide‐aided ultrasonic pretreatments and mono‐ultrasonication (US), were used to rupture the microalgal cells for extracting cellular inclusion. The disruption efficiency and the energy consumption of each technique were estimated through measuring the amount of released protein from cells and the microscopic images after pretreatment. Results showed that the combined pretreatments obtained a much higher lysis efficiency than did the US (over twofold). However, the concentration of H2 O2 used (ranging from 0.1 to 5 mM) failed to influence the lysis efficiency significantly ( P < 0.05). Additionally, the acoustic energy efficiency was increased with the initial cell concentration treated, but the coefficient of utilization of algal biomass was decreased significantly. Therefore, an ideal initial cell concentration (13.4 × 10 7 cells/mL) was gained in terms of the higher coefficient of utilization of algal biomass. This research suggested that a synergistic technique could be an effective pretreatment for microalgal cell disruption and downstream comprehensive utilization. © 2017 Curtin University of Technology and John Wiley & Sons, Ltd.